Forecasting the COVID-19 mortality rate worldwide: a comparison of univariate models / Elya Sara Syuhada Azhar ... [et al.] - Azhar, Elya Sara Syuhada; Mohamed Yusof, Noreha; Che Sulaiman, Nur Salsabila; Rosli, Siti Nuraqina (UiTM Cawangan Negeri Sembilan, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the SARS-CoV-2 virus. COVID- 19 disease was initially discovered in Wuhan, China and now spread throughout the countries. Most people infected with the virus will develop mild to moderate respiratory problems and recover without the need for special treatment. However, some people will become severely ill and require medical treatment and can cause death. COVID-19 mortality rates nationwide are increasing day by day and growing concerns. On 13 December 2021, 5,325,079 deaths worldwide were recorded. Thus, this study is regarding the mortality rate of COVID-19 using univariate forecasting techniques. The data was retrieved from GitHub Our World in Data. Holt's method was selected as the best univariate model in order to forecast the mortality rate. Holt's method shows the lowest error measures. The predicted value of the mortality rate for COVID-19 is decreasing between 1 November 2021 to 31 January 2022. The decreasing predicted value might be due to the vaccinated programs done worldwide. A further study should be done to measured the factors related to the improved spread of COVID-19.